FENOMENOLOGI STRATEGI PERAN GANDA PERAWAT PEREMPUAN TERHADAP KINERJA PERAWAT DI MASA PANDEMI COVID-19. STUDI KASUS: RSUD KOTA DEPOK - Putri Irayani, (2022)
Currently, Indonesia is facing the covid-19 pandemic, which causes nurses to be able to maintain professional performance. For female nurses who are married and have children, they must carry out dual roles at the same time during this covid-19 pandemic, namely as housewives and as nurses. Challenges and appropriate strategies are needed to be able to support success in carrying out their roles and maintain professional performance as a nurse. For this reason, this study aims to see how the strategy in carrying out a dual role on the success of performance as a nurse at the Depok City General Regional Hospital. This research uses a qualitative approach with interview, observation, and document review techniques to analyze the dual role of female nurses on the performance of nurses during the covid-19 pandemic at the Depok City General Regional Hospital. The resource persons in this research were 12 people who were married female nurses and had children, the head of the room, and nurse co-workers. Data were analyzed in 3 stages, namely data reduction, data presentation, and drawing conclusions. Data validity using triangulation technique. The results showed that female nurses who had dual roles had the right strategy to carry out their roles as housewives and nurses so that the performance of female nurses who had dual role the covid-19 pandemic at the Depok City General Regional Hospital was considered good.